Effect Of Plastering And Carbon Fibre Reinforced Polymer (CFRP) On Concrete Masonry Prism Strength Capacity - Yusof, Mohd Anuar Mohd (Universiti Sains Malaysia, 2017)
Brick is an important material in the construction of particular buildings and it is widely used in all parts of the world over the last century until today. The use of these materials is closely related to several factors, among which are easily obtained, cheap and easy job control. There are some effects that arise through the use of brick in building construction. For the purposes of the study, a total of 12 units of bond brick for prism in architecture, using concrete blocks of dimensions 390 mm x 190 mm x 190 mm unit and each specimen that is built has a height of 1 metre, the specimens are classified into controlled specimen without any plaster, one sided plastered, two sided plastered, and specimen strengthened by Carbon Fibre Reinforced Polymer (CFRP) strip in vertical orientation. The mixing ratio of the materials used for the production of mortar for the use of bonding and rendering are the same and tests conducted in accordance with ASTM C 1437 to ensure that the characteristics of the were resulting set is the same and controlled. During the tests performed, the effects of the resulting pressure is observed and recorded. The results of observations and tests found the average value of the failure load is as follows (A) 180 kN, (B) 175 kN, (C) 209 kN, and (D) 198 kN. The conclusion that can be made is strength group (C) is the highest but crack pattern could be controlled compared to the group (D) in which the pattern of cracks is vertical and can be expected.